Pengembangan Bahan Ajar Berbasis Pendekatan Content and Language Integrated Learning (CLIL) pada Pembelajaran Menulis Puisi Siswa Kelas IV SDN 86 Kaur - Ahmad Fadilah; Abdul Muktadir; Puspa Djuwita (Universitas Bengkulu, 2023)
The development research model used is the Borg and Gall model. The instruments in this study were documentation, interviews, teacher and student response questionnaire validation sheets. Based on the results of research and development, it can be concluded that the teaching materials developed are valid and feasible to use. The average aspect of the presentation of the analysis obtained an Aiken's V coefficient with a score of 0.98, with the criteria of